Standardizing Physiological Indicators’ Tests for High School Students In Baghdad - Rahman, Barq (Journal of Physical Education, 2018)
Standardizing Physiological Indicators’ Tests for High School Students In BaghdadThe problem of the researcher lies in the out of date criteria used by the ministry of education in high schools concerning physical education tests. The aim of the research is to standardize physiological indicators’ tests for high school students in Baghdad. The researcher sued the descriptive method. The subjects were (209) high school students aged 16 – 18 years old from (40) schools in Baghdad. The data was collected and treated using SPSS to conclude that the criteria and standards of this research can be used for selecting league players in different sports and events as well as the ability to divided students according levels based on their physiological indicators. Finally he recommended making similar studies on primary and secondary schools in Iraq and other governorates.